Computational color imaging : 7th International Workshop, CCIW 2019, Chiba, Japan, March 27-29, 2019, Proceedings /: 7th International Workshop, CCIW 2019, Chiba, Japan, March 27-29, 2019, Proceedings. (2019) - Unknown
No abstract available